Assessing the detection capability of a dense infrasound network in the southern Korean Peninsula. Issue 2 (22nd May 2017) - Che, Il-Young; Le Pichon, Alexis; Kim, Kwangsu; Shin, In-Cheol
Abstract: The Korea Infrasound Network (KIN) is a dense seismoacoustic array network consisting of eight small-aperture arrays with an average interarray spacing of ∼100 km. The processing of the KIN historical recordings over 10 yr in the 0.05–5 Hz frequency band shows that the dominant sources of signals are microbaroms and human activities. The number of detections correlates well with the seasonal and daily variability of the stratospheric wind dynamics. The quantification of the spatiotemporal variability of the KIN detection performance is simulated using a frequency-dependent semi-empirical propagation modelling technique. The average detection thresholds predicted for the region of interest by using both the KIN arrays and the International Monitoring System (IMS) infrasound station network at a given frequency of 1.6 Hz are estimated to be 5.6 and 10.0 Pa for two- and three-station coverage, respectively, which was about three times lower than the thresholds predicted by using only the IMS stations. The network performance is significantly enhanced from May to August, with detection thresholds being one order of magnitude lower than the rest of the year due to prevailing steady stratospheric winds. To validate the simulations, the amplitudes of ground-truth repeated surface mining explosions at an open-pit limestone mine were measured over a 19-month period. Focusing on the spatiotemporal variability of the stratospheric winds which control to first order where infrasound signals are expected to be detected, the predicted detectable signal amplitude at the mine and the detection capability at one KIN array located at a distance of 175 km are found to be in good agreement with the observations from the measurement campaign. The detection threshold in summer is ∼2 Pa and increases up to ∼300 Pa in winter. Compared with the low and stable thresholds in summer, the high temporal variability of the KIN performance is well predicted throughout the year. Simulations show that the performance of the global infrasound network of the IMS is significantly improved by adding KIN. This study shows the usefulness of dense regional networks to enhance detection capability in regions of interest in the context of future verification of the Comprehensive Nuclear-Test-Ban Treaty.